The extreme C terminus of herpes simplex virus DNA polymerase is crucial for functional interaction with processivity factor UL42 and for viral replication. - Digard, P (1993)
The herpes simplex virus DNA polymerase is composed of two subunits, a large catalytic subunit (Pol) and a smaller subunit (UL42) that increases the processivity of the holoenzyme. The interaction between the two polypeptides is of interest both for the mechanism by which it enables the enzyme to synthesize long stretches of DNA processively and as a possible target for the rational design of novel antiviral drugs. Here, we demonstrate through a combination of insertion and deletion mutagenesis that the carboxy-terminal 35 amino acids of Pol are crucial for binding UL42. The functional importance of the interaction was confirmed by the finding that a pol mutant defective for UL42 binding retained polymerase activity, but did not synthesize longer DNA products in the presence of UL42. Moreover, several association-incompetent mutants failed to complement the replication of a pol null mutant in a transient transfection assay, confirming that the Pol-UL42 interaction is necessary for virus replication in vivo and therefore a valid target for directed drug design.